Factors regulating bone remodeling processes in aseptic implant loosening. Issue 2 (8th May 2016) - Hartmann, Eliza S.; Köhler, Miriam I.; Huber, Felicitas; Redeker, Julia I.; Schmitt, Baerbel; Schmitt‐Sody, Marcus; Summer, Burkhard; Fottner, Andreas; Jansson, Volkmar; Mayer‐Wagner, Susanne
ABSTRACT: This study was undertaken to screen periprosthetic tissues (PPTs) under specified conditions for a series of molecular components and describe them in bone remodeling processes within aseptic loosening. PPT samples were obtained from patients undergoing revision surgery of endoprostheses ( n  = 24) and synovial tissues from patients with OA (control) ( n  = 18), patients with any form of inflammatory arthritides were excluded. Tissue samples were examined via microbiology, histology (H&E, TRAP), immunohistochemistry (CD68/anti‐S100a4), quantitative real‐time PCR (ALP, COL1A1, cathepsin K, M‐CSF, MMP13, OPG, RANK, RANKL, TNF‐α, and TRAP) and an endotoxin‐assay. PPT samples contained a variety of cellular components and stained positive for TRAP (56%), CD68 (100%), and S100a4 (100%). Wear debris were found in cells staining positive for CD68 and S100a4. In PPTs significantly higher ALP, COL1A1, MMP‐13, RANK, RANKL, and TRAP expression were found along with a significantly higher RANKL/OPG ratio and a significantly lower OPG expression. No significant difference was observed for M‐CSF, TNF‐α, cathepsin K, and endotoxin levels. In conclusion we found osteogenic proteins (ALP, COL1A1), a proteolytic enzyme (MMP‐13), markers for osteoclast differentiation (RANK, RANKL), and osteoclast activity (TRAP) to be increased in PPT, whereas OPG expression decreased significantly in comparison to control. We present data about a large series of molecular components in PPT and describe novel and key findings about their expression levels in regards to aseptic implant loosening. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:248–257, 2017.